MODEL KUAT TEKAN, POROSITAS DAN KETAHANAN AUS PROPORSI LIMBAH PELEBURAN BESI DAN SEMEN UNTUK BAHAN DASAR PAVING BLOCK - Dermawan, Moch. Husni (Semarang State University, 2011)
Abstract: Utilization of iron smelting waste has not been fully utilized for building materials,Ã‚Â especially as an ingredient in the manufacture of paving block stacking. The purpose of this studyÃ‚Â was to characterize the slag and to determine compressive strength, porosity, wear resistance ofÃ‚Â paving blocks by using slag as a sand substitute. The method used by experimental methods.Ã‚Â Preparation of specimens made 2 types of test object without slag and specimens with slagÃ‚Â content. The specimens made 4 treatment research slag content of 20%, 40%, 60%, and 80%.Ã‚Â Each group was made of samples, 5 for compressive strength, 5 porosity and 5 wear resistance.Ã‚Â Testing is done at BPIK Semarang. Test results from block paving with slag content of 0% showsÃ‚Â the compressive strength of 204.24 kg / cm Ã‚Â², 4.95% porosity, resilience auas 0.145 mm / min. SlagÃ‚Â content of 20%, compressive strength of 192.13 kg / cm Ã‚Â², 6.150% porosity, wear resistance 0.186Ã‚Â mm / min. Slag content of 40%, compressive strength of 179.33 kg / cm Ã‚Â², 7.657% porosity, wearÃ‚Â resistance 0.259 rnm / min. Slag content of 60%, compressive strength of 164.94 kg / cm Ã‚Â², 8.509%Ã‚Â porosity, wear resistance 0.3482. 80% slag content of compressive strength of 149.06 kg / cm Ã‚Â²,Ã‚Â 9.911% porosity, wear resistance 0.448 mm / min. Compressive strength of paving blocks with slagÃ‚Â content of 20% and 40% belong to the quality of III, the porosity of the paving block 20% slagÃ‚Â content is categorized in the quality of III, and wear resistance of paving blocks slag content of 20%belong to the quality of III.Keywords: compressive strength, wear resistance, porosity, paving blockÃ‚Â Abstrak: Pemanfaatan limbah peleburan besi belum dimanfaatkan secara maksimal untuk bahanÃ‚Â bangunan, khususnya sebagai bahan susun dalam pembuatan paving block. Tujuan dalamÃ‚Â penelitian ini adalah untuk mengetahui karakteristik terak dan untuk mengetahui kuat tekan,Ã‚Â porositas, ketahanan aus paving block dengan menggunakan terak sebagai bahan substitusi pasir.Ã‚Â Metode yang digunakan dengan metode eksperimen. Pembuatan benda uji dibuat 2 jenis yaituÃ‚Â benda uji tanpa terak dan benda uji dengan kandungan terak. Benda uji penelitian dibuat 4Ã‚Â perlakuan kandungan terak yaitu 20%, 40%, 60%, dan Ã‚Â 80%. Tiap kelompok dibuat benda uji, 5Ã‚Â untuk kuat tekan, 5 porositas dan 5 ketahanan aus. Pengujian dilakukan di BPIK Semarang. HasilÃ‚Â pengujian dari paving block dengan kandungan terak 0% menunjukkan kuat tekan 204,24 kg/cmÃ‚Â²,Ã‚Â porositas 4,95%, ketahanan auas 0,145 mm/menit. Kandungan terak 20%, kuat tekan 192,13Ã‚Â kg/cmÃ‚Â², porositas 6,150%, ketahanan aus 0,186 mm/menit. Kandungan terak 40%, kuat tekanÃ‚Â 179,33 kg/cmÃ‚Â², porositas 7,657%, ketahana aus 0,259 rnm/menit. Kandungan terak 60%, kuatÃ‚Â tekan 164,94 kg/cmÃ‚Â², porositas 8,509%, ketahanan aus 0,3482. Kandungan 80% terak kuat tekanÃ‚Â 149,06 kg/cmÃ‚Â², porositas 9,911%, ketahanan aus 0,448 mm/menit. Kuat tekan paving block denganÃ‚Â kandungan terak 20% dan 40% tergolong dalam mutu III, porositas paving block kandungan terakÃ‚Â 20% tergolong dalam mutu III, dan ketahanan aus paving block kandungan terak 20% tergolongÃ‚Â dalam mutu III.Kata Kunci: kuat tekan, keausan, porositas, paving block